(INVESTIGATING THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON THE RISK OF FINANCIAL HELPLESSNESS IN COMPANIES LISTED ON THE IRAQI STOCK EXCHANGE) (World Bulletin of Management and Law, 2022)
The purpose of this research is to investigate the impact of corporate social responsibility on the risk of financial distress in companies listed on the Iraqi stock exchange. The statistical population under investigation consists of 20 companies admitted to the Iraqi Stock Exchange, which were selected for the 7-year period of 2014-2020. The independent variable in this research is the social responsibility of the company and the dependent variable is financial helplessness. After determining the research method, the required information was collected by using the real data taken from the financial statements of the Iraqi stock companies and finally by using the software version 10 of this data and information. was analyzed. The results of examining the hypothesis of this research showed that corporate social responsibility has a negative and significant effect on the helplessness of Iraqi stock exchange companies. Therefore, it can be said that by disclosing the information related to the social responsibility of companies, it is possible to prevent the bankruptcy and financial helplessness of the companies admitted to the Iraqi Stock Exchange
Keywords: Corporate; responsibility; helplessness; Exchange